Morphological Characteristics of Tidal Creeks in the Central Coastal Region of Jiangsu, China, Using LiDAR - Bingxue Zhao (Remote Sensing, 2019)
Tidal creeks are an important component of the intertidal zone and are essential for maintaining the balance between sedimentary processes and the hydrodynamic environment. A quantitative analysis of the morphological characteristics of tidal creeks is essential for understanding their processes of evolution and to evaluate the stability of tidal flats. This study describes the morphological characteristics of tidal creeks using a high-resolution airborne LiDAR DEM. The parameters include the number, order, length, width, depth, and width/depth ratio. The results show that the number and degree of development tidal creeks along the central coast of Jiangsu are higher than those in the radial sandbanks, and the mean width and length increase with the increasing tidal creek order. The number, length, and depth of tidal creeks in the salt marsh zone with well-developed vegetation are higher than those areas with little vegetation cover. The number of tidal creeks in the mid-upper intertidal zone is the largest, while the length and width of tidal creeks in the lower intertidal zone are the greatest. The differences in these characteristics are mainly related to the vegetation distribution, tidal flat width, and hydrodynamic conditions. Our findings potentially provide guidelines for coastal management and the evaluation of tidal flat stability.